Purified Vero cell rabies vaccine and human diploid cell strain vaccine: comparison of neutralizing antibody responses to post-exposure regimens - Suntharasamai, Pravan (1986)
Neutralizing antibody responses to conventional rabies post-exposure regimens of human diploid cell strain vaccine (HDCSV) and the new purified Vero cell rabies vaccine (PVRV) were compared in 58 healthy Thai veterinary students. The geometric mean titres (GMTs) of the group given HDCSV were slightly higher than those given PVRV, but on day 28 the peak GMTs of the two groups were statistically similar. The early antibody response to PVRV was unaffected by the addition of passive immunization, whereas the level of HDCSV response was reduced on day 14, so that there was no difference on that day between the GMTs of the two vaccine groups given HRIG. However, by day 91 the GMT of those given PVRV and HRIG was lower than in those given HDCSV alone or with HRIG. The appearance of antibody was less rapid than was observed in previous studies using multiple-site intradermal vaccination. Side effects were trivial. Our results confirm the promise of this new, potentially more economical tissue culture vaccine, but they suggest that the regimen could be improved.